Luminescence of blood leukocytes fluorochromated with acridine orange of operated patients in the dynamics of emotional, anesthetic, and surgical stress - Fedotov, E.; Aleksandrova, K.; Vasylyev, D.; Frolov, O.; Vavrysevych, J.; Gutyj, B.; Yaremko, O.; Magrelo, N.; Sus, H.; Vus, U.; Федотов, Євген Рудольфович; Александрова, Катерина Вячеславівна; et al. (My University, 2021)
The dynamics of luminescence indices of blood leukocytes, fluorochromated with acridine orange, were studied in operated patients. The most informative of them was the luminescence intensity at 640 nm to characterize the state of immunity. It radically increased during the traumatic periods of the operation and during the activation of reparative processes. Significant radical changes of I = 640 nm in blood lymphocytes, which occurred during the traumatic period of the operation, persisted for a week after the operation, indicating the degree of participation of the immune system in reparative regeneration.
Keywords: acridine orange; leukocyte; stress